Reflektif Penderitaan Ayub Sebagai Resiliensi Iman Kristen: Membangun Pondasi Kekristenan - Arifianto, Yonatan Alex (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: The story of Job in the Bible depicts a person who has a life of good character and fears God but experiences physical and spiritual suffering and distress, despite experiencing Job's suffering he is found to remain faithful to follow God. Even though he didn't understand all the things he was going through, he was still willing to be patient and persevere, Amidst his illness, losing all his possessions and being abandoned by his family and friends. But Job still expressed his faith that God was his helper. The purpose of this writing is to be able to inspire faith and belief in Job's suffering as a reflection of the resilience of the Christian Faith in building the foundations of present-day Christianity. Using descriptive qualitative research methods with a literature study approach, it can be concluded that the existence of suffering as part of the life of true believers is a reflection of what Job experienced, namely suffering as the resilience of Christian faith: efforts to build Christian foundations are: First, Christianity is able to provide a definition and is able to understand as the correct paradigm of Job and his suffering. Furthermore, believers can face the challenges of Christian faith and suffering in the present era where they see and emulate Job's suffering, both perseverance and faith as a reflection of Job's example for the resilience of today's Christian faith. Abstrak: Kisah Ayub di dalam Alkitab yang menggambarkan seorang pribadi yang memiliki kehidupan yang berkarakter baik dan takut akan Allah namun mengalami penderitaan dan kesusahan jasmani maupun rohani, walaupun mengalami penderitaan Ayub didapati tetap setia mengikut Tuhan. Sekalipun ia tidak mengerti semua hal yang ia alami, tetapi dia masih mau sabar dan bertekun, Di tengah kondisinya yang sakit, kehilangan semua harta benda dan ditinggal oleh keluarga dan teman-temannya. Namun Ayub tetapi menyatakan imanya Bahwa Tuhan adalah penolongnya. Tujuan penulisan ini untuk dapat menggugah iman dan kepercayaan orang percaya dari penderitaan Ayub. Sehingga sebagai reflektif akan resiliensi Iman Kristen dalam membangun pondasi kekristenan masa kini.Mengunakan metode penelitian kualitatif deskritif dengan pendekatan studi literature. Maka Hasil temuan penelitian pada artikel adalah adanya penderitaan sebagai bagian dari kehidupan orang percaya sejatinya menjadi reflektif atas apa yang dialami oleh Ayub yaitu penderitaan sebagai resiliensi iman kristen: upaya membangun pondasi kekristenan adalah: Pertama kekristenan mampu memberikan definisi dan mampu memahami sebagai paradigma yang benar tentang Ayub dan penderitaannya. Selanjutnya orang percaya dapat menghadapi tantangan iman Kristen dan penderitaan di era masa kini dimana melihat dan meneladani penderitaan Ayub baik ketekunan dan Iman sebagai refleksi keteladanan Ayub bagi resiliensi iman kristen masa kini.